Development of signals influencing the growth and termination of thalamocortical axons in organotypic culture. - Molnár, Z; Blakemore, C (1999)
Explants of embryonic or postnatal rat cortex, organotypically cultured in serum-free medium, maintain their structural integrity and their upper layers continue to mature. Coculture of portions of embryonic thalamus with cortical slices taken at different ages reveals a temporal cascade of cortical signals. (1) Slices of occipital cortex taken at E19 or earlier stimulate axonal outgrowth from explants of embryonic lateral geniculate nucleus but do not allow the fibers to invade. (2) In cortical slices taken after E19 but before P2, thalamic axons enter the slice, from any direction, and extend radially across the entire depth of the cortical plate without branching or terminating. (3) In slices taken after P2, fibers slow down, arborize, and terminate in the maturing layer 4 of the cortex. If the thalamic explant is placed against the pial surface of the cortical slice, axons still enter and branch in the same layer. These findings imply that the developing cortex expresses a diffusible growth-promoting factor and then itself becomes growth permissive, and finally the maturing layer 4 expresses a "stop signal." In triple cocultures of one thalamic explant with a "choice" of two neighboring slices, thalamic axons will not invade slices of cerebellum but behave indistinguishably in response to slices from any region of the hemisphere. Thus the initial tangential distribution of the thalamic projection in vivo (which is achieved by about E16) is unlikely to be controlled by regional variation in signals produced by the cortex. When cortical slices were precultured alone for 7-14 days before the addition of an explant of embryonic thalamus for 4 further days of coculture, the pattern of innervation was more appropriate to the chronological age of the slice than the age at which it was first taken. Thus the timing of the cascade of cortical properties is at least partly intrinsically determined. This sequence of expression of these signals suggests that they play a part in vivo in controlling the outgrowth of thalamic fibers, their accumulation under the cortical plate, their invasion of the plate, and their arborization in layer 4.